2021
DOI: 10.1016/j.jiac.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Prospective analytical performance evaluation of the QuickNavi™-COVID19 Ag for asymptomatic individuals

Abstract: Introduction: Antigen testing may help screen for and detect severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections in asymptomatic individuals. However, limited data regarding the diagnostic performance of antigen tests for this group are available. Methods: We used clinical samples to prospectively evaluate the analytical and clinical performance of the antigen test QuickNavi™-COVID19 Ag. This study was conducted at a PCR center between October 7, 2020 and January 9, 2021. Two nasopharyngeal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“… **Not explicitly stated, but as per inclusion criteria only study participants who are asymptomatic. ††The study reported by Kiyasu et al 54 is specified as ‘extension study’ of a previous study reported by Takeuchi et al . 50 Both studies were included in this systematic review and considered as two separate studies due to different but overlapping recruitment periods, substantial differences in the proportion of paediatric study participants who were symptomatic and differences in how discordant RT-PCR test results were re-evaluated.…”
Section: Resultsmentioning
confidence: 99%
“… **Not explicitly stated, but as per inclusion criteria only study participants who are asymptomatic. ††The study reported by Kiyasu et al 54 is specified as ‘extension study’ of a previous study reported by Takeuchi et al . 50 Both studies were included in this systematic review and considered as two separate studies due to different but overlapping recruitment periods, substantial differences in the proportion of paediatric study participants who were symptomatic and differences in how discordant RT-PCR test results were re-evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The reactivity of antigen tests can differ between clinical and UTM™ samples. QuickNavi™-COVID19 Ag detected the virus in almost all clinical samples with Ct values <30 when the supplied extraction reagent was used [ 7 , 18 ], but the sensitivity plummeted when samples were diluted in UTM™ [ 19 ]. Measuring the limit of detection seems insufficient to verify the clinical performance of antigen tests.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we enrolled participants and collected samples at the PCR center in Tsukuba Medical Center Hospital (TMCH) between March 25 and July 5, 2021, which intensively collected nasopharyngeal samples for the PCR analysis of SARS-CoV-2 [ [5] , [6] , [7] , [8] , [9] ]. Subjects referred by 59 primary care facilities and a local public health center, as well as TMCH healthcare workers with suspected SARS-CoV-2 infection based on symptoms or a known contact history with COVID-19 confirmed/suspected patients were prospectively enrolled.…”
Section: Methodsmentioning
confidence: 99%